Atualizações da Netflix na internet: múltiplas flâneries - Braghini, Kélliana (Universidade do Vale do Rio dos Sinos, 2018)
This research aimed to understand how Netflix are updated on the internet through its audiovisualities. The Netflix audiovisualities are thought of in this research from the Bergsonian intuition (BERGSON, 2005; DELEUZE, 2004) as virtuality in becoming in memory, potentially updateable in any time and in any materiality. In this dissertation, we have analyzed Netflix's duration, that is, its existence as a multiple of multiples, and from the frame methodology (KILPP, 2003; 2010), and as part of it, the cartographic flâneries (BENJAMIN, 2006) is updated on the internet. Our research course, which has gone through many empirical and theoretical-methodological comings and goings, led us to the construction of three constellations, which show three ways of acting of the Netflix’s audiovisualities. These are: “Netflix’s framing on the Platform”; “Netflix’s framing on Social Networking Websites” and “Netflix’s framing dispersed on the internet”. As a result of the montage operated inside the constellations, we could see, as a dialectical image, the main form of updating of Netflix’s on the internet, which condenses the three modes and their frames: a spatially-temporally mounted data stream in the user audiovisual experience.
Keywords: Audiovisualidades; Experiência audiovisual; Flâneries; Fluxo; Netflix; Audiovisualities; Flâneries; Flow; Audiovisual experience; Netflix; ACCNPQ::Ciências Sociais Aplicadas::Comunicação